Demand response capacity constrained optimisation of multicast routing in smart grid. (20th August 2020) - Zhu, Zihao; Li, Xiaohui; Ding, Yuemin; Liu, Zhenxing
Low-latency Demand Response (DR) operation is urgently required to maintain grid stability in the context of wide area control for smart grids. Multicast-based communications are a feasible choice for reducing DR communication delay. Traditional multicast routing algorithms that only consider constraints such as bandwidth or delay will cause users with large DR capacities to need more time to perform DR operations, resulting in increased power grid frequency amplitude and adjustment time. To address this issue, a systematic approach, namely minimum Bandwidth Tree with delay and DR capacity constraint (BTDR), is presented in this paper. It enables the node with large DR capacity to connect to the multicast tree with high priority in the process of constructing the multicast tree, reducing the response time of the DR device with large DR capacity. Simulations are conducted to demonstrate the approach presented in this paper.